Zakat Barang Tambang: Tak Ada Istilah “Uang Panas” Hanya Berkah atau Tidak: Penyuluhan zakat terhadap penambang emas Desa Tanoyan Selatan, Bolaang Mongondow. - Muhibuddin; Rahman, Supandi; Muhammad Syarif Djauhari; Riska Octavia Habie (Komunal Jurnal Pengabdian Masyarakat, 2024)
This outreach program aims to increase the understanding and awareness of miners in South Tanoyan Village regarding mining zakat obligations. This counseling will involve local religious figures and zakat experts from academic circles at IAIN Sultan Amai Gorontalo, with material covering the definition of zakat, mandatory zakat requirements, types of zakat, and how to calculate mining zakat. Through this outreach, it is hoped that miners can pay zakat correctly and contribute to improving the welfare of the local community. This counseling is carried out using lecture, discussion and simulation methods. After counseling, a final survey was conducted to evaluate the increase in participants' understanding. The survey results show a significant increase in their understanding of mining zakat.